Colapso esférico em presença de energia escura. - Rocha Junior, Mario (2017)
It is a known fact that the Universe goes through of expansion where there is strong evidences that the presence of the so-called dark energy is responsible for accelerating this processe. From this point of view, this work aims to use the spherical collapse theory to study the behaviour of a structure, here know as overdensity immersed in a Friedmann-Robertson-Walker background universe. Considering its density as an ideal fluid whose state equation is p = w? we will initially apply the theory in an Einstein-de Sitter Universe and then proceed to the universe model with presence of dark energy where we will analyze the ?CDM and the wCDM models with specific values for the constant w.